KEPASTIAN HUKUM TERHADAP KEKUATAN ALAT BUKTI AKTA DI BAWAH TANGAN - FATIN FATIN; FENCE M. WANTU; SRI NANANG MEISKE KAMBA (Universitas Mahasaraswati K. Mataram, 2024)
This research aims to: 1) analyze and determine the legal certainty strength of private deeds as evidence in resolving civil disputes. 2) understand the legal consequences of using private deeds as evidence based on Article 1874 of the Civil Code. The research employs the normative method, which reviews secondary document studies such as laws and regulations and court decisions involving private deeds as evidence. It is based on the theory of evidence, legal certainty, and expert opinions, which are then analyzed using qualitative methods.The results of the legal analysis on the strength of private deeds as evidence in the District Court of Gorontalo City are as follows: 1) private deeds are considered legitimate evidence, but their evidentiary strength in judicial processes requires the involvement of several parties that must be included in the private deed, namely: a) Both parties involved, b) Authorized officials (Land Deed Officials, Notaries, and Local Government), and c) Witnesses. 2) According to Article 1874 of the Civil Code, all forms of private deeds carry legal consequences in judicial processes. Therefore, to mitigate negative outcomes from using private deeds as evidence, it is necessary to apply the appropriate procedures during their creation to ensure legal certainty in resolving civil cases